The influence of temperature on the effects induced by Triclosan and Diclofenac in mussels - Freitas, Rosa (2020)
Little is known about the consequences of exposure to pharmaceuticals and personal care products (PPCPs) in elevated temperatures associated with climate change. To increase the knowledge on this topic, Mytilus galloprovincialis mussels were exposed to 1.0 µg/L of either the antimicrobial Triclosan (TCS) or the pharmaceutical drug Diclofenac (DIC), at control (17ºC) and 4ºC raised (21ºC) temperatures for 28 days. Triclosan and DIC concentrations in the water and tissues were subsequently measured and related to biomarker responses including: energy metabolism (electron transport system (ETS) activity, glycogen and protein reserves), oxidative stress markers, glutathione balance between the reduced and the oxidised form (GSH/GSSG), and damage to proteins and lipids. Mussels responded to the increase in temperature and drug exposure by lowering their metabolic rate (decreased ETS), increasing their endogenous reserves and antioxidant defences, thus preventing oxidative stress damage, with the exception of DIC exposure at the higher temperature. In all cases, GSH/GSSG ratio was reduced in detriment of the antioxidant form at both PPCPs exposures and elevated temperature with no additive effect due to combined stressors. Overall, either drug exposure or increased temperature could compromise the ability of mussels to withstand further insults.